Mycobacterium tuberculosis–Specific Antigen Rv3619c Effectively Alleviates Allergic Asthma in Mice - Safar, Hussain A.; El-Hashim, Ahmed Z.; Amoudy, Hanady; Mustafa, Abu Salim (Frontiers in Pharmacology, 2020)
Despite significant advances, asthma remains a cause of premature death, and current treatments are sub-optimal. Antigen-specific Th2 cells and their cytokines are primary mediators of the pathophysiological changes seen in asthma. Studies in animal models have shown that mycobacteria can suppress asthma-like features by preventing development of asthma via alteration of the Th1/Th2 cytokines ratio. In this study, we evaluated the efficacy of immunization with Mycobacterium tuberculosis-specific antigen Rv3619c, utilizing a Th1 delivery system, to modulate the allergic airway inflammation in a Th2-driven model of asthma. The rv3619c gene was cloned in an expression plasmid pGES-TH-1, expressed in Escherichia coli, and the recombinant protein Rv3619c was purified to homogeneity using affinity chromatography. Mice were immunized with the recombinant proteins emulsified in Freund’s Incomplete Adjuvant (IFA) alone and in combination with low dose dexamethasone and challenged with ovalbumin (OVA). Airway inflammation was assessed by quantifying airway cytology, histological changes and Th2 cytokine (IL-5) secretion from splenocytes. OVA-specific IgE, IgG and IgG1 from sera was assessed, as well as pERK1/2 expression in the lung tissue. Immunization with recombinant Rv3619c alone and in combination with low dose dexamethasone effectively inhibited the OVA-induced increase in total cell counts, eosinophil airway cell infiltration in BAL fluid, perivascular and peribronchial inflammation and fibrosis, and goblet cell hyper/metaplasia. In addition, Rv3619c/IFA inhibited the OVA-induced IL-5 in spleen cells, OVA-specific IgE, IgG and IgG1 levels in sera, and pERK1/2 expression in lung tissue. Taken together, this study demonstrated that Rv3619c/IFA may be an effective vaccine for the prevention of asthma.